PENGEMBANGAN PROFESIONALISME DALAM MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN DI SEKOLAH MENENGAH KEJURUAN (SMK) BINA PUTRA MANDIRI PARUNG PANJANG BOGOR - Lutfi Ashyari; Sahlani Sahlani; Iqbal Ubaidillah; Sahro Sahro; Hasan Basri (STKIP Pesisir Selatan, 2026)
The study aims to analyze the development of professionalism in the management of educators and education personnel at Sekolah Menengah Kejuruan Bina Putra Mandiri Parung Panjang Bogor. Professionalism development is an essential aspect in improving the quality of vocational education, particularly in preparing competent graduates who are ready to face the demand of the industrial world. This research uses a qualitative approach with a case study method to obtain an in-depth understanding of management practices related to teacher and education staff development. Data were collected through observation, interviews, and documentation, involving school leaders, teachers, and administrative staff. The findings show that professionalism development is implemented through various programs such as training workshops, academic supervision, in-house training, and performance evaluation. The principal plays a key role as an instructional leader in planning and implementing human resource developments programs. However, several challenges were identified, including differences in teachers digital competencies and limited access to training resources. Overall, the study concludes that professionalism development in the school has begin implemented quite well but still requires continuous improvement to achieve optimal educational quality.